Public Attitudes and Awareness of Services Labeled as Halal: Sikap dan Kesadaran Masyarakat Terhadap Jasa yang Berlabel Halal - Syahriani, Novita; Khamal Rokan, Mustapa (Perisai : Islamic Banking and Finance Journal, 2023)
This research was conducted to find out impact of people's attitudes and awareness on the halal label. Research method used in this study is quantitative research combined with narrative research, where this study aims to determine the correlation between attitudes, consumer enlightenment, and halal label. Result can be used as a result of hypothesis testing data, the Standardized coefficient value in the table is -.034 with a significant value indicating that the behavioral variable (X1) does not have a significant effect on the halal label (Y). Therefore, hypothesis 4 suspects that the attitude has a positive effect on the halal label is not supported. using the results of hypothesis testing data, the Standardized coefficient value in the table is .663 with a significant value sharing that the citizen awareness variable (X2) has a significant influence on the halal label (Y), in which the assumption of public awareness has a positive effect on the halal label is supported. Hypothesis 1 which has an attitude variable is not supported, therefore it does not have a positive effect on the halal label. Hypothesis 2 is supported, due to the assumption that citizen awareness has a significant/influence on the halal label.